IMPLEMENTASI SIKAP SPIRITUAL DAN SIKAP SOSIAL DALAM SISTEM FULL DAY SCHOOL - Ufara Rizki Pranjia; Indah Maria Ulpa; Suci Putri Manthika (Jurnal Pendidikan Islam, 2020)
The 2013 curriculum development, which is oriented towards character through the competency aspects of spiritual and social attitude, is the application of the full day school system in several schools in Indonesia. Thus, this study aims to elaborate the implementation of spiritual and social attitudes with a Full Day School system. This qualitative research employed a case study design in Al-Munir Islamic Junior High School in Bekasi, West Java. Data collection techniques were carried out by interview, observation, and documentation. For the data analysis, the model of Miles and Hubberman was employed including the stages of reducing data, presenting data, and drawing conclusions. The results showed that the implementation of spiritual attitudes and social attitudes in a full day school system was carried out by (1) planning the programs of student character development; (2) implementing the programs of student character development; and (3) evaluating the programs of student character development, which consists of internal and external assessments of Teaching and learning activities